(untitled) (Research, Society and Development, 2022)
Early edentulism represents a public health problem, since the negative effects are not limited to aesthetic issues, but also to the stomatognathic system, phonetics, postural condition and bone structures. Based on a data collection, this research sought to point out and discuss the proportion of edentulism, as well as the implications for quality of life. Data on oral health conditions in adults between 19 and 35 years of age were analyzed, the collection instrument consisted of an analysis of secondary data (dental records) made available at the secretary of the school clinic located at CURES/CEPACA – Cancer Prevention Center. After data collection, an increase in tooth loss was observed proportional to age without distinction of sex, according to the medical records, the age at which the greatest tooth loss occurred was at 34 years, presenting as main factors associated with caries and periodontal disease, and only 3% had all healthy teeth. Thus, given the data found, it is understandable that the results obtained can help in the formulation of public policies aimed at promoting the oral health of the population of the municipality of Vitória de Santo Antão, since caries and periodontal disease are diseases that already have preventive methods. established and should be introduced as early as possible through programs in the community and in the family nucleus.